2014
DOI: 10.1093/jpids/piu098
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Reactogenicity of an Inactivated Quadrivalent Influenza Vaccine Administered Intramuscularly to Children 6 to 35 Months of Age in 2012–2013: A Randomized, Double-Blind, Controlled, Multicenter, Multicountry, Clinical Trial

Abstract: BackgroundInfluenza attack rates are high in 6- to 35-month-old children; vaccines containing both lineages of influenza B (Yamagata and Victoria), in addition to the H3N2 and H1N1 antigens, may improve protection rates.MethodsIn a randomized double-blind controlled trial, the immunogenicity and reactogenicity of an inactivated quadrivalent influenza vaccine (QIV) and a trivalent control vaccine (TIV) were assessed.ResultsSix hundred one children (QIV, n = 299; TIV, n = 302) were enrolled at 8 sites in 3 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Some previous studies have suggested that pain at the injection site may be modestly increased with QIV compared with TIV or hepatitis A vaccine [25, 30], whereas others report similar levels of pain [21, 23, 26, 27]. The incidence of fever was similar with both vaccines, consistent with previous published studies [25, 30].…”
Section: Discussionsupporting
confidence: 86%
“…Some previous studies have suggested that pain at the injection site may be modestly increased with QIV compared with TIV or hepatitis A vaccine [25, 30], whereas others report similar levels of pain [21, 23, 26, 27]. The incidence of fever was similar with both vaccines, consistent with previous published studies [25, 30].…”
Section: Discussionsupporting
confidence: 86%
“…Injection site pain was modestly more common with Q-IIV4 (>30%) than D-IIV3 control (>20%) in children aged 3-17-years after the first dose. In the two randomized controlled phase II studies of Q-IIV4 in children aged 6-35 months, [69,70] the frequencies of both injection site and systemic AEs including fever, notable for its link with febrile seizures, following vaccination were comparable in the Q-IIV4 and IIV3 recipients, after dose 1 or 2, and across the age strata (6−17 months and 18 −35 months of age). [71] In all studies, [57,[67][68][69][70][71] regardless of age group, the rates of unsolicited AEs over 21 −28 days after vaccination and of medically attended and SAE during the entire clinical trials were comparable between Q-IIV4 and control groups.…”
Section: Reactogenicity and Safetymentioning
confidence: 99%
“…There have been two additional controlled trials of Q-IIV4 in children aged 6−35 months to support its eventual licensure in this group beyond Canada and Mexico. Overall, immunogenicity data are available for adults aged ≥18 years, [67,68] children aged 3-17 years, [69] and children aged 6-35 months [69][70][71] (Supplementary File 3).…”
Section: Q-iiv4mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, GSK has developed two quadrivalent influenza vaccines in parallel, Fluarix and Flulaval, for which immunogenicity data are similar [29][30][31][32], and one VE study using Flulaval was done which showed that the influenza vaccine was efficacious in preventing influenza in children, but failed to show a benefit of quadrivalent compared to trivalent vaccine [33].…”
Section: Expert Commentarymentioning
confidence: 99%